Pancytopenia de to Sheehan’s Syndrome - Amir, Radia; Altaf, Sara; Amir, Radia (International Journal of Pathology, 2018)
Abstract: Sheehan’s syndrome is hypopituitarism caused by anterior pituitary necrosis dueto hemorrhage leading to hypovolemic shock during or after childbirth. We present a case of a 32-year old ladywho developed severe post partum hemorrhage after child-birth, eight years back. Since then she has progressivelydeveloped symptoms of anemia and now she has presented to us with pancytopenia. Anemia is the most commonhematological disorder known to be associated with Sheehan’s syndrome, however pancytopenia is rarely reported.